The Role of Milk Components, Pro-, Pre-, and Synbiotic Foods in Calcium Absorption and Bone Health Maintenance - Ilesanmi-Oyelere, Bolaji L.; Kruger, Marlena C. (Frontiers in Nutrition, 2020)
Increasing peak bone mass during adolescence and reducing bone loss in later life are two approaches to reduce the risk of osteoporosis with ageing. Osteoporosis affects a large proportion of the elderly population worldwide and the incidence is increasing. Milk consumption is an accepted strategy in building peak bone mass and therefore may reduce the risk of osteoporosis. In childhood calcium, phosphorous and growth factors are the important components to support bone growth but in adults the positive influence on bone density/maintenance may also be due to other bioactive proteins/peptides or lipids in milk acting directly in the gastrointestinal tract (GIT). Lactose has been known to increase calcium absorption; galactooligosaccharides (GOS) are derived from lactose and are nondigestible oligosaccharides. They have been shown to improve mineral balance and bone properties as well as causing increases in bifidobacteria in the gut, therefore a prebiotic effect. Supplementation with fortified milk and dairy products with added prebiotics, increased both calcium and magnesium absorption and caused some modulation of gut microbiota in animals and humans. Fermented milk is now also recognized to contain highly active components such as vitamins, peptides, oligosaccharides and organic acids. In this review, the role of milk and milk components in improving calcium absorption and thereby supporting bone health is discussed. In addition, some reference is made to combining the inherent beneficial components from milk with fortificants/nutrients that will support bone health through adulthood. Novel data suggesting differences in diversity of the microbiota between healthy and osteoporotic women are provided.